2019
DOI: 10.21608/smj.2019.41383
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of internet addiction with anxiety, depression and personality traits –Upper Egypt study

Abstract: Objective:The aim of the study was to investigate the relationship of Anxiety, Depression and personality traitswith Internet addiction (IA) inuniversity students. Methods:A cross-sectional survey was conducted on a random sample of 588 students selected from four faculties in Sohag University. IAwas assessed by the 20item Young Internet Addiction Test (YIAT). Information was also collected on socio-demographics, university-related factors and Internet usage patterns. Eysenck personality questionnaire (EPQ)use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…A cross-sectional survey of 587 medical students at Sohag University reported that 47.7% engaged in pathological Internet usage based on Young's IAT (Ali et al, 2017). Another study at Sohag University found that 35.2% of students had problematic IA, including 27.04% and 39.29% (n = 154) in applied and theoretical programs (Azab et al, 2019). Further, a clinical study among 60 students at Al-Azhar University found moderate and severe IA in 46.7% and 3.3%, respectively (Mohamed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey of 587 medical students at Sohag University reported that 47.7% engaged in pathological Internet usage based on Young's IAT (Ali et al, 2017). Another study at Sohag University found that 35.2% of students had problematic IA, including 27.04% and 39.29% (n = 154) in applied and theoretical programs (Azab et al, 2019). Further, a clinical study among 60 students at Al-Azhar University found moderate and severe IA in 46.7% and 3.3%, respectively (Mohamed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Table (4) shows that 44.7% of adolescents experienced occasional or frequent problems followed by an average of online user among 43.3% among the adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Kim et al [6] reported that the proportion of participants who experienced a depressive episode, suicidal ideation, and suicidal attempt were 38.0%, 19.1%, and 4.8%, respectively, while suicidality in our study is assessed to be 1.2%. Another study performed in Egypt on Sohag University, 588 students showed that 86.9% of students with PIU had anxiety and 85.02% of students with PIU significantly had depression; this could be explained by the academic overload and the high pressure of study demands that these university students are facing [33].…”
Section: Discussionmentioning
confidence: 99%